The Effectiveness of SQ3R in Teaching Reading Comprehension - zuhridin yuliandi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
This article aims at knowing which one the higher of students’ score in reading comprehension taught by SQ3R method and conventional method. This research used quasi-experimental research design. The subject of this study is VIII C as experimental group and VIII B as control group. The tests were given to the students in the form of pre-test and post-test. The test was in multiple choice items. The instruments were developed on the basis of materials and topic given in the 2nd semester of eight grade students. The finding of this research is there are significant difference students’ score, it can be concluded that post-test score of experimental group were higher than control group. So, by using SQ3R method could assits the students acquired better score in reading comprehension and SQ3R gave good contributions to make students felt much better to comprehend the text.